PELATIHAN MANAJEMEN USAHA UNTUK MENIGKATKAN DAYA SAING KEPADA PARA PELAKU USAHA INDUSTRI KECIL DAN MENENGAH (UMKM) RANGINING DI DESA KADU GADUNG KECAMATAN CIPEUCANG KABUPATEN PANDEGLANG - Suhandi Suhandi; Iqbal Iqbal; Siti Fatonah; Siti Afifah; Linda Juliani Hidayat; Ira Fitriana Sari (LPPM Universitas Bina Bangsa, 2021)
Abstrac The majority of the residents of Kadu Gadung Village are farmers and rangining business actors, but their management is still simple and not managed systematically and well planned, so that they cannot provide maximum results. The purpose of this training is to increase competitiveness for industrial business actors small and medium scale rangining towards independent small industries. The implementation method is through: seminars for delivering material, discussions, practices, mentoring, monitoring and evaluation. The results of this training show that not all small and medium rangining industrial business actors in Kadu Gadung Village, which has not yet taken care of distribution permits, halal certificates, produces product innovations and online marketing, due to limited funds and human resources